Risk Analysis of Broiler Chicken Farming with a Partnership Model (Case Study of Risky Astiani's Business in Jawi-Jawi Village, Bulukumpa District, Bulukumba Regency) - Asti Octaviana; Reni Fatmasari Syafruddin; Nurdin Nurdin; Sri Mardiyati; Saleh Molla (PT FORMOSA CENDEKIA GLOBAL, 2026)
The broiler chicken farming business plays a vital role in Indonesia’s livestock sector but is exposed to high risks, particularly production, price, and financial risks. This study aims to analyze the types and levels of business risks and to examine risk mitigation strategies in broiler chicken farming businesses operating under a partnership system. This study employs a case study approach focused on the Risky Astiani Broiler Chicken Farm, located in Jawi-Jawi Village, Bulukumpa Subdistrict, Bulukumba Regency. Data were collected from four informants (one owner and three workers) using purposive sampling. The probability and impact of risks were measured using a Likert scale, then analyzed using the Severity Index (SI) and Risk Score (SR = P × D), and mapped onto a probability–impact matrix. The results indicate three main risks: production risk, price risk, and financial risk. Price risk falls into the high category, while production risk and financial risk fall into the moderate category. Risk mitigation efforts were implemented through enhanced daily monitoring, improved management of closed-house systems, intensified coordination with partner companies, and better financial planning. Although partnerships can reduce uncertainty regarding inputs and marketing, farmers’ weak bargaining position in price setting remains a major vulnerability affecting business sustainability.